2-(Trifluoroacetyl) thiophene as an electrolyte additive for high-voltage lithium-ion batteries using LiCoO2 cathode. (15th October 2020) - Sun, Yi; Huang, Jian; Xiang, Hongfa; Liang, Xin; Feng, Yuezhan; Yu, Yan
Highlights: The 2-(Trifluoroacetyl) thiophene (TFPN) has been developed as a functional electrolyte additive. Introduction of 0.5 wt% TFPN into the electrolyte can greatly enhance the cycling performance of high-voltage LiCoO2 cathode. Addition of 0.5 wt% TFPN can effectively suppress the decomposition of both electrolyte solvent and lithium salt. Abstract: The development of high voltage electrolytes plays a critical role to achieve advanced lithium ion batteries with high energy density. Application of suitable electrolyte additives is a facile and effective way to achieve enhanced electrochemical performance at high voltage operation. In this work, 2-(trifluoroacetyl) thiophene (TFPN) was investigated as a functional electrolyte additive for high performance lithium ion batteries using high-voltage LiCoO2 cathode. When cycled between 3.0 V and 4.4 V at 0.5 C, the capacity retention of the LiCoO2 cathode significantly increases from 33.2 %–90.6 % by the addition of 0.5 wt% TFPN into the baseline electrolyte. Based on the measurements on impedance spectra and X-ray photoelectron spectra, the improved cycling performance is attributed to the preferential oxidation of TFPN on the cathode surface and thus form a protective layer to suppress the decomposition of both electrolyte solvent and lithium salt. This work presents that TFPN has great potential as functional additive for the development of high-voltage and high-energy-density lithium ion batteries.